2021
DOI: 10.1016/j.breast.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological response to neoadjuvant therapies and pathological complete response as a biomarker of survival in human epidermal growth factor receptor-2 enriched breast cancer – A retrospective cohort study

Abstract: Background: Human epidermal growth factor receptor-2 (HER2) is overexpressed in 20e25% of breast cancers. Complete eradication of disease following neoadjuvant therapies and chemotherapy has been referred to as pathological complete response (pCR). Aims: To determine clinicopathological predictors of pCR to neoadjuvant therapies and to evaluate pCR as a surrogate to enhanced survival. Methods: Consecutive female patients with HER2 positive (HERþ) breast cancer managed surgically in a single institution between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Furthermore, the discovery and development of diagnostic, prognostic and therapeutic biomarkers have transformed the international perception such that at least four heterogeneous molecular subtypes are recognised in clinical practice [11,12]. Distinguishing these subtypes relies on the genetic expression of estrogen receptor (ER) status, progesterone receptor (PgR) status, human epidermal growth factor receptor-2 (HER2) status, and Ki-67 proliferation indices due to their critical role in the substratification, prognostication, and personalization of treatment modalities for each subtype [10,[12][13][14][15][16][17][18][19]. Mandatory ER, PgR, and HER2 immunohistochemical appraisals are recommended to approximate the genetic expression of these in all cases of invasive breast cancer according to the American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) guidelines [20,21], as these are established predictive and prognostic biomarkers in breast oncology, proving crucial in therapeutic decision making [18,[22][23][24].…”
Section: Introduction Biomarkersmentioning
confidence: 99%
“…Furthermore, the discovery and development of diagnostic, prognostic and therapeutic biomarkers have transformed the international perception such that at least four heterogeneous molecular subtypes are recognised in clinical practice [11,12]. Distinguishing these subtypes relies on the genetic expression of estrogen receptor (ER) status, progesterone receptor (PgR) status, human epidermal growth factor receptor-2 (HER2) status, and Ki-67 proliferation indices due to their critical role in the substratification, prognostication, and personalization of treatment modalities for each subtype [10,[12][13][14][15][16][17][18][19]. Mandatory ER, PgR, and HER2 immunohistochemical appraisals are recommended to approximate the genetic expression of these in all cases of invasive breast cancer according to the American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) guidelines [20,21], as these are established predictive and prognostic biomarkers in breast oncology, proving crucial in therapeutic decision making [18,[22][23][24].…”
Section: Introduction Biomarkersmentioning
confidence: 99%
“…While the molecular era has shifted the paradigm toward encompassing intrinsic biological tumour parameters which inform treatment decisions and prognoses, the degree of disease burden remains paramount to preoperative surgical planning. The routine measurement of the ER, PgR, HER2 receptors and Ki-67 proliferation indices [ 62 , 63 , 64 ] furthers accurate prognostication through intrinsic molecular subtyping, with modern advances implicating features pertinent to the tumour microenvironment important in informing prognosis [ 65 ]. Several studies detail miRNA expression profiles in breast cancer tissue, outlining their importance in relation to nodal burden, disease recurrence and survival [ 58 , 66 , 67 ].…”
Section: Mirna In Predicting Outcome In Operable Breast Cancermentioning
confidence: 99%
“…Oncological practice has evolved recognising the inherent value of treating patients with chemotherapy in the neoadjuvant setting. Advantages of neoadjuvant chemotherapy (NAC) included tumour downstaging, increasing patient eligibility for breast conservation surgery (BCS), as well as the generation of in vivo data in relation to tumour sensitivity, which has been illustrated to carry prognostic significance for disease recurrence and overall survival (OS) [ 52 , 53 , 54 ]. While DFS and OS outcomes are similar to those treated in the adjuvant setting, recent data from a meta-analysis of randomised trials conducted by the Early Breast Cancer Triallist’s Collaborative Group (EBCTCG) indicate that there are increased rates of locoregional recurrence (LRR) following neoadjuvant therapy (21.4% vs. 15.9%) [ 55 ].…”
Section: Breast Cancer Chemotherapymentioning
confidence: 99%
“…As previously outlined, breast oncology has evolved in recent years to recognise it is strategic and advantageous to treat patients with chemotherapy in the neoadjuvant setting [ 57 , 58 ]. While conventional clinicopathological characteristics have been reported to correlate with response to NAC [ 53 , 81 , 82 , 83 ], deciphering those likely to achieve such responses remains challenging to the oncologists, with response rates often difficult to predict. Several recent studies correlate miRNA expression profiles with response to NAC for breast cancer: Xing et al reported that increased expression of miR-23a-3p, miR-200c-3p, miR-214-3p and reduced expression of miR-451a and miR-638 correlated to chemoresistance (Miller–Payne grade 1) [ 84 ].…”
Section: Micrornas In Predicting Response To Neoadjuvant Chemotherapiesmentioning
confidence: 99%